PERLINDUNGAN HUKUM PIHAK KETIGA SEBAGAI PEMBELI DALAM LELANG SEBAGAI BARANG SITAAN YANG MENJADI OBJEK JAMINAN FIDUSIA - NURLIANI NURLIANI (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Sutiarnoto3. T. Keizerina Devi A According to executorial title, the receiver of fiduciary can directly execute the collateral through public auction without going to the court. Auction has advantage compared to other kind of sale, namely fair, quick and safe; and it achieves the highest price and provides legal certainty. This is a normative juridical research. It is a legal research that uses secondary data; started with the analysis of legal problems from either books or laws. The legal protection for the third party is obtained by filing a lawsuit first. The other legal efforts are by submitting objection to the auction office and leasing company; and filing a claim for indemnity for the money that has been paid to buy the auction object.Keywords: Legal Protection, Auction, Confiscated Goods, Fiduciary